Three-dimensional atomic orbital plots in the classroom using Winplot - Chung, Wilfredo Credo (Animo Repository, 2013)
The Winplot software makes the relationship between an atomic orbital and the wave function of a hydrogen-like atom easy to understand. This relationship can be quickly demonstrated in the classroom. © 2013 The American Chemical Society and Division of Chemical Education, Inc.